Developing Critical Thinking and Learning Achievements in Science of Grade Nine Students Using 5E Learning Cycle with 3D Interactive Model - Orteza, Gerome; Saripa, Aree; Jai-on, Kittisak (ASEAN Journal of Education, 2025)
This study aimed to: (1) evaluate students' critical thinking relative to a 75% criterion, (2) assess learning achievement against an 80% criterion, and (3) investigate student satisfaction with the 5E learning cycle and 3D interactive model for the unit on “Electrical Energy”. Participants included 60 Grade 9 (M3) students from the English Programme at Benjamarachutit School, enrolled in the second semester of the 2023 academic year. A class of 30 students was selected through cluster random sampling. The study employed a one-group posttest-only design, with a 12-hour intervention using 5E learning cycle lesson plans with 3D interactive models. Data were collected through a critical thinking test, learning achievement test, and satisfaction questionnaire, and analyzed using a One Sample t-test and descriptive statistics to compare mean and standard deviation. Results showed that the intervention significantly enhanced critical thinking and learning achievement, with mean scores of 81.50% and 94.17%, respectively (p < .05). Additionally, students reported a “Completely Satisfied” level of satisfaction with the 5E learning cycle and 3D model. These findings suggest that the 5E learning cycle with a 3D interactive model is effective in developing critical thinking components such as inference, recognition of assumption, deduction, interpretation, and evaluation of arguments, as well as the six levels of revised Bloom’s taxonomy.